Предмет: Математика,
автор: erasyl200708
(a-6)²+(a+3)(a-5)+7 памагите
Ответы
Автор ответа:
1
Ответ:
2a^2 - 14a + 28
Пошаговое объяснение:
(a-6)²+(a+3)(a-5)+7 = a^2 - 12a +36 + a^2 - 5a + 3a - 15 + 7 = 2a^2 - 14a + 28
Автор ответа:
0
Ответ:
Пошаговое объяснение:
Формула : -
( x - y ) = x² + y² - 2xy
Здесь,
x = a
b = 6
( a - 6 )²
= a² + 6² - 2 ( 6 ) ( a )
= a² + 36 - 12a
= a² - 12a + 36
Формула : -
( x + z ) ( x + y ) = x² + ( z + y )x + ( z ) ( y )
Здесь,
x = a
z = 3
y = - 5
( a + 3 ) ( a - 5 )
= a² + ( 3 - 5 )a + ( 3 ) ( 5 )
= a² - 2a + 15
( a - 6 )² + ( a + 3 ) ( a - 5 ) + 7
= a² - 12a + 36 + a² - 2a + 15 + 7
= a² + a² - 12a - 2a + 15 + 36 + 7
= 2a² - 14a + 58
Похожие вопросы
Предмет: Русский язык,
автор: buNalexandusha8
Предмет: Английский язык,
автор: Алина89121380883
Предмет: Українська література,
автор: k2lopNastyaMaken
Предмет: Химия,
автор: hhhhh39
Предмет: Математика,
автор: Nastya123563